Implementation of Al-Miftah Lil Ulum Method for Reading Yellow Books in The Book Room Darul Huda Islamic Boarding School Mayak Tonatan Ponorogo - Budiono, Budiono (Jurnal Paradigma, 2025)
Darul Huda Mayak Islamic Boarding School is a boarding school that uses the salafiyatil hadithah method. In the process of understanding yellow books, at least one must master the science of nahwu and sharaf, because these two sciences are the main gateways to understanding and studying various yellow books. At Darul Huda Mayak Islamic Boarding School, the Al-Miftah lil ulum method has been applied, a basic method to get to know in depth the rules of nahwu and sharaf which are arranged practically. This study aims to analyze (1) the application of the Al-Miftah lil ulum method in learning yellow books at Darul Huda Mayak Islamic Boarding School; (2) supporting factors and inhibiting factors in the application of the Al-Miftah lil ulum method at Darul Huda Mayak Islamic Boarding School; and (3) the implications of the application of the Al-Miftah lil ulum method in learning yellow books at Darul Huda Mayak Islamic Boarding School. This study uses a descriptive qualitative approach with data collection methods using Observation, Interviews and Documentation. Data analysis using data reduction, data presentation, drawing conclusions, verification, developing model building models, compiling write-up reports). Data validity techniques using technical triangulation and source triangulation. Based on the results of data analysis, it was found that (1) the Al-Miftah method was applied in the book room of the Darul Huda Mayak Islamic Boarding School by combining lecture, singing, and memorization techniques. In addition, there are also four strategies applied, namely understanding and memorizing material, learning songs, takror and questions and answers, and innovative game strategies.